The Centriole’s Role in Miscarriages - Avidor-Reiss, Tomer; Achinger, Luke; Uzbekov, Rustem (Frontiers in Cell and Developmental Biology, 2022)
Centrioles are subcellular organelles essential for normal cell function and development; they form the cell’s centrosome (a major cytoplasmic microtubule organization center) and cilium (a sensory and motile hair-like cellular extension). Centrioles with evolutionarily conserved characteristics are found in most animal cell types but are absent in egg cells and exhibit unexpectedly high structural, compositional, and functional diversity in sperm cells. As a result, the centriole’s precise role in fertility and early embryo development is unclear. The centrioles are found in the spermatozoan neck, a strategic location connecting two central functional units: the tail, which propels the sperm to the egg and the head, which holds the paternal genetic material. The spermatozoan neck is an ideal site for evolutionary innovation as it can control tail movement pre-fertilization and the male pronucleus’ behavior post-fertilization. We propose that human, bovine, and most other mammals–which exhibit ancestral centriole-dependent reproduction and two spermatozoan centrioles, where one canonical centriole is maintained, and one atypical centriole is formed– adapted extensive species-specific centriolar features. As a result, these centrioles have a high post-fertilization malfunction rate, resulting in aneuploidy and miscarriages. In contrast, house mice evolved centriole-independent reproduction, losing the spermatozoan centrioles and overcoming a mechanism that causes miscarriages.